Functionality of Two Origins of Replication in Vibrio cholerae Strains With a Single Chromosome - Bruhn, Matthias; Schindler, Daniel; Kemter, Franziska S.; Wiley, Michael R.; Chase, Kitty; Koroleva, Galina I.; Palacios, Gustavo; Sozhamannan, Shanmuga; Waldminghaus, Torsten (Frontiers in Microbiology, 2018)
Chromosomal inheritance in bacteria usually entails bidirectional replication of a single chromosome from a single origin into two copies and subsequent partitioning of one copy each into daughter cells upon cell division. However, the human pathogen Vibrio cholerae and other Vibrionaceae harbor two chromosomes, a large Chr1 and a small Chr2. Chr1 and Chr2 have different origins, an oriC-type origin and a P1 plasmid-type origin respectively, driving the replication of respective chromosomes. Recently, we described naturally occurring exceptions to the two-chromosome rule of Vibrionaceae: i.e., Chr1 and Chr2 fused single chromosome V. cholerae strains, NSCV1 and NSCV2, in which both origins of replication are present. Using NSCV1 and NSCV2, here we tested whether two types of origins of replication can function simultaneously on the same chromosome or one or the other origin is silenced. We found that in NSCV1, both origins are active whereas in NSCV2 ori2 is silenced despite the fact that it is functional in an isolated context. The ori2 activity appears to be primarily determined by the copy number of the triggering site, crtS, which in turn is determined by its location with respect to ori1 and ori2 on the fused chromosome.